Verdi's Aida : the history of an opera in letters and documents - Busch, Hans, 1914-1996; Verdi, Giuseppe, 1813-1901 (University of Minnesota Press, 1978)
This is a detailed account of the creation and production of the opera Aida as revealed in he letters and documents of the composer Guiseppe Verdi and his associates. Aida was given its European premiere at La Scala in 1872, and the correspondence concern.